Fluorine-containing polymer and piezoelectric film and preparation method thereof
By co-conjugating the photoelectric conjugated compound in polyvinylidene fluoride and secondary polarization under ultrasonic conditions, a fluoropolymer piezoelectric film with high voltage electrical properties and high temperature resistance was prepared, which solves the problem that polymer piezoelectric materials in the prior art are difficult to take into account between high voltage electrical strain constant and high usage temperature.
Patent Information
- Application Number
- CN202311185830.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-14
AI Technical Summary
The existing polymer piezoelectric materials are difficult to balance between high voltage electrical strain constant and high operating temperature, and their energy reception efficiency is limited in the ultrasonic field.
A specific amount of photoconjugated compounds is copolymerized in polyvinylidene fluoride, and a thin film is prepared by extrusion and tensile strength, and after prepolarization in an alternating electric field, it is secondary polarized under ultrasonic conditions to form a fluoropolymer piezoelectric film with high voltage electrical properties and high temperature resistance.
The electrical displacement and piezoelectric properties of the piezoelectric film are improved, the piezoelectric properties at high temperatures are enhanced, and the contradiction between high voltage electrical properties and high usage temperatures of polymer piezoelectric materials is solved.
Smart Images

Figure CN119613601A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymers, and in particular to a fluorine-containing polymer and a piezoelectric film thereof and a preparation method thereof. Background Art
[0002] Among all kinds of piezoelectric materials, PVDF polymer piezoelectric materials have three advantages: first, high flexibility, its compliance coefficient is dozens of times that of piezoelectric ceramic materials, and it can be made into large and thin films; second, high mechanical strength and toughness, which can withstand large impact forces; third, high voltage electric strain constant, which can be used to make highly sensitive flexible receiving transducers and transducer arrays. The piezoelectric properties of polymers can be improved by adding trifluoroethylene (TrFE) monomer to prepare poly (vinylidene fluoride-trifluoroethylene) (P (VDF-TrFE)), but the heat resistance of P (VDF-TrFE) is not as good as that of PVDF homopolymer.
[0003] In order to solve the problems of high voltage electric strain constant and high operating temperature of polymer piezoelectric materials, the prior art has made the following efforts:
[0004] Patent document CN110462859A discloses a piezoelectric film and a method for manufacturing the same. The piezoelectric film is prepared from a P (VDF-TrFE) mixture with different polymerization ratios, but still cannot resolve the contradiction between the high voltage electric strain constant and the high operating temperature.
[0005] Ultrasonic polarization is a new polarization method used in inorganic compounds such as barium titanate, but has not been used in the field of fluorine-containing polymers. This is mainly because inorganic piezoelectric ceramics are a narrow bandgap material. In the force field and electric field generated by the ultrasonic field, the electrons and holes inside are easily separated and oriented. However, the bandgap of pure PVDF or P (VDF-TrFE) is wider, and its ability to receive the force field and electric field energy generated by ultrasound is limited. Summary of the invention
[0006] The inventors of the present invention have discovered that a fluorine-containing polymer obtained by copolymerizing a specific amount of photoelectric conjugated compounds in polyvinylidene fluoride can be obtained by extrusion and stretching to obtain a film. The film has piezoelectric properties after pre-polarization in an AC electric field. Secondary polarization is carried out under ultrasonic conditions. The obtained fluorine-containing polymer piezoelectric film becomes soft, the electric displacement is increased, and the piezoelectric performance is improved. In addition, the fluorine-containing polymer piezoelectric film still maintains piezoelectric properties at high temperatures, which solves the contradiction between the high piezoelectricity and high operating temperature of polymer piezoelectric materials.
[0007] PVDF polymer has limited ability to receive force field and electric field energy generated by ultrasound. By copolymerizing photoelectric conjugated compounds, the photoelectric conjugated compounds as defects in the PVDF chain segment interrupt the long-range ordered structure of VDF, which is conducive to the formation of a β conformation with ferroelectric piezoelectricity. At the same time, it can promote the formation of more permanent structural defects in the polymer in the ultrasonic force field. At the same time, the photoelectric conjugated compounds copolymerize into the VDF chain segment to form p-type semiconductor materials, which can improve the photoelectric effect of the polymer, improve the energy coupling efficiency of the polymer, and improve the efficiency of energy reception in the ultrasonic field. It can also serve as an energy trap in the material to capture and fix polarized charges, increase the overall number of dipoles in the material, and thus improve the effect of ultrasonic polarization.
[0008] The invention provides a fluorine-containing polymer, which comprises a vinylidene fluoride structural unit and a photoelectric conjugated compound structural unit. The photoelectric conjugated compound is selected from at least one of N-vinyl carbazole (VCZ), vinyl naphthalene, vinyl thiophene or vinyl anthracene.
[0009] The vinylnaphthalene is selected from at least one of 1-vinylnaphthalene and 2-vinylnaphthalene.
[0010] The vinylthiophene is selected from at least one of 2-vinylthiophene and 3-vinylthiophene.
[0011] The vinylanthracene is selected from at least one of 1-vinylanthracene, 2-vinylanthracene and 9-vinylanthracene.
[0012] The content of the photoelectric conjugated compound structural unit in the fluorine-containing polymer is 0.5-10 mol%. When the content of the photoelectric conjugated compound structural unit is less than 0.5 mol%, the number of monomers is too small, the photoelectric effect is limited, and the secondary polarization has little effect on the polymer; when the structural unit content is greater than 10 mol%, the photoelectric conjugated compound can significantly reduce the crystallinity of the polymer, destroy the ferroelectric domain, and rapidly reduce the piezoelectric properties of the entire material because it cannot form a eutectic with VDF. In order to improve the piezoelectric properties of the material, preferably, the content of the photoelectric conjugated compound structural unit is 1-5 mol%.
[0013] The weight average molecular weight of the fluorine-containing polymer is 200,000 to 700,000, preferably 250,000 to 350,000.
[0014] The polydispersity index (PDI) of the fluorine-containing polymer is 1.5 to 5, preferably 2.1 to 3.0.
[0015] The melt index of the fluorine-containing polymer is 5 to 10, preferably 7.1 to 8.2.
[0016] The present invention also provides a piezoelectric film, which comprises a fluorine-containing polymer, wherein the fluorine-containing polymer includes a vinylidene fluoride structural unit and a photoelectric conjugated compound structural unit, and the photoelectric conjugated compound is selected from at least one of N-vinyl carbazole, vinyl naphthalene, vinyl thiophene or vinyl anthracene.
[0017] The present invention also provides a method for preparing a fluorine-containing polymer piezoelectric film, the preparation method comprising the following steps:
[0018] S1: The fluorinated polymer is extruded in a molten state to obtain a fluorinated polymer sheet, which is then stretched to obtain a fluorinated polymer film;
[0019] S2: After the fluorine-containing polymer film is polarized in an alternating electric field, it is polarized for a second time under ultrasonic conditions with a power of 250 to 350 W for 18 to 30 minutes to obtain a fluorine-containing polymer piezoelectric film.
[0020] In step S1, the thickness of the fluorine-containing polymer sheet is 100-200 μm, the stretching ratio of the fluorine-containing polymer sheet is 3-6 times, and the thickness of the fluorine-containing polymer film is 20-70 μm.
[0021] In step S2, the frequency of the AC electric field is 0.5-5 Hz, and the intensity of the AC electric field is ≥400 MV / m.
[0022] In step S2, the fluorine-containing polymer film is polarized for a period of ≥40 under an alternating electric field to ensure that the fluorine-containing polymer film is fully polarized.
[0023] The fluorine-containing polymer of the present invention is secondarily polarized under ultrasonic conditions. On the one hand, the transient, high-frequency ultra-high ultrasonic pressure can cause PVDF to produce permanent structural defects and structural charges. On the other hand, the concurrently generated electric field can polarize the defects of PVDF and capture the generated polarization charges in the structural defects. The use of ultrasound to perform secondary polarization on the material on the basis of corona polarization can further promote the improvement of the piezoelectric properties of the material.
[0024] In one embodiment, in step S1, the fluorine-containing polymer is a pellet.
[0025] In another embodiment, in step S1, the fluorine-containing polymer is a powder, and before melt extrusion, the powder is granulated into pellets by a screw extruder.
[0026] The present invention also provides a method for preparing a fluorine-containing polymer, wherein the method is a suspension polymerization method and comprises the following steps:
[0027] (1) adding deionized water, a dispersant, a telogen, and a photoelectric conjugated compound accounting for 1.64 to 14.29 wt % of the total amount of the photoelectric conjugated compound and vinylidene fluoride into a reaction kettle, and replacing the reaction kettle with nitrogen three times after closing the kettle;
[0028] (2) adding 98.36 to 85.71 wt % of the total amount of the photoelectric conjugated compound and the vinylidene fluoride into the reaction kettle, and then starting to raise the temperature to 35 to 50° C.;
[0029] (3) Adding an initiator to the reactor, maintaining the polymerization reaction temperature at 35-50° C. and the initial pressure at 5.8-7.0 MPa, and when the pressure drops to 2.5 MPa, ending the polymerization reaction, washing, dehydrating, and drying to obtain a fluorine-containing polymer.
[0030] The dispersant is selected from at least one of methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose or maleic acid modified polyethylene.
[0031] The telogen is selected from at least one of methanol, isopropanol, acetone, ethyl acetate, diethyl carbonate, dimethyl carbonate, dichloromethane or n-hexane.
[0032] The initiator is selected from at least one of di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate, diisobutyl peroxydicarbonate, 2-ethylhexyl peroxydicarbonate, di-tert-butyl peroxide, tert-butyl peroxybenzoate or lauroyl peroxide.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] By introducing photoelectric conjugated compound structural units into PVDF, it can better absorb the energy generated by the ultrasonic probe under ultrasonic conditions. The obtained fluorinated polymer piezoelectric film has an increased electric displacement value and improved piezoelectric performance. In addition, the piezoelectric film can still maintain its piezoelectric properties at high temperatures. The piezoelectric performance and heat resistance of the obtained piezoelectric film are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a curve showing the change of piezoelectric strain constant of the pre-polarized polymer film in Example 8 of the present invention after ultrasonic polarization at different ultrasonic powers of 0 to 400 W.
[0036] Figure 2 This is a curve showing the change in piezoelectric strain constant of the pre-polarized polymer film of Example 9 of the present invention after polarization at different ultrasonic times of 0 to 40 min at an ultrasonic power of 300 W.
[0037] Figure 3This is a curve showing the change of piezoelectric strain constant at different temperatures for the piezoelectric film prepared in Example 4 of the present invention.
[0038] Figure 4 The electrodeformation curves of the pre-polarized polymer film in Example 9 of the present invention after being polarized at different ultrasonic times of 0, 5 min, 10 min, and 20 min at an ultrasonic power of 300 W. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.
[0040] The fluorine-containing polymer performance test methods in the examples and comparative examples of the present invention are as follows:
[0041] Weight average molecular weight test method: PL-50 room temperature GPC test was used, the mobile phase was chromatographic pure DMF, and the standard curve was prepared using polystyrene standard samples.
[0042] Test method for β-crystal content in fluorinated polymers: Agilent Cary 630 infrared spectrometer was used with a test wave number of 400 to 4000 cm -1 .
[0043] Testing method for piezoelectric strain constant of fluoropolymer at different temperatures: Using Radiant Technologies' Premiere II ferroelectric testing system (driving voltage of 0-10 kV), with MTI Instruments' MTI 2100 one-dimensional laser sensor and ChemGlass' CG-1999-V-10 heating stage.
[0044] Example 1: P(VDF-VCZ)-99.5 / 0.5
[0045] 3000mL of deionized water, 1g of hydroxypropyl methylcellulose as a dispersant, 3g of ethyl acetate as a telogen and 20g of N-vinyl carbazole were added to the reactor, the reactor was closed and replaced with nitrogen three times; 1200g of vinylidene fluoride was added to the reactor respectively, and then the temperature was raised; when the temperature rose to 40°C, 5g of diisopropyl peroxydicarbonate was added to the reactor as an initiator to initiate the polymerization reaction, the initial reaction pressure was 6.6MPa, the reaction temperature was maintained at 40°C, and the reaction was terminated when the pressure dropped to 2.5MPa. After the polymerization was completed, the fluorinated polymer powder was obtained by washing, dehydration and drying. The fluorinated polymer obtained by nuclear magnetic resonance characterization contained 0.5mol% of N-vinyl carbazole copolymer structural units.
[0046] The obtained fluorine-containing polymer powder was added into a twin-screw extruder, the temperature of the screw heating section was set to 200°C, 210°C and 220°C respectively, and the rods were prepared by extrusion through a circular die. The rods were passed into a plastic crusher and crushed into pellets.
[0047] Fluorine-containing polymer pellets were added to the twin-screw extruder, and the temperatures of the screw heating section were set to 200°C, 210°C and 220°C, respectively. The fluorine-containing polymer pellets were extruded through a flat die in a molten state to obtain a 150 μm sheet. The extruded polymer sheet was pulled and uniaxially stretched in the stretching section with a stretching ratio of 6 to obtain a 30 μm polarization film.
[0048] The film was spread flat on the negative electrode plate with a distance of 5 mm from the discharge needle. The frequency was 1 Hz and the electric field strength amplitude was gradually increased from 0 to 400 MV / m of alternating current and maintained for 80 seconds. The electric field was then removed to obtain a prepolarized polymer film. The piezoelectric strain constant was tested to be 24.1 pm / V.
[0049] The film was placed in an ice water bath and fixed to the bottom of the container with double-sided tape. The ultrasonic probe was inserted 2 mm above the film. The output power of the probe was set to 300 W. The working mode was 5 s every 6 s for 20 min. After ultrasonic polarization, the film was taken out and dried. The piezoelectric strain constant was tested to be 28.0 pm / V.
[0050] Example 2: P(VDF-VCZ)-99 / 1
[0051] 3000mL of deionized water, 1g of hydroxypropyl methylcellulose as a dispersant, 3g of ethyl acetate as a telogen and 40g of N-vinyl carbazole were added to the reactor, the reactor was closed and replaced with nitrogen three times. 1200g of vinylidene fluoride was added to the reactor respectively, and then the temperature was raised. When the temperature rose to 40°C, 5g of diisopropyl peroxydicarbonate was added to the reactor as an initiator to initiate the polymerization reaction. The initial reaction pressure was 6.8MPa. The reaction temperature was maintained at 40°C, and the reaction was terminated when the pressure dropped to 2.5MPa. After the polymerization was completed, the fluorinated polymer powder was obtained by washing, dehydration and drying. The fluorinated polymer obtained by nuclear magnetic resonance characterization contained 1mol% of N-vinyl carbazole copolymer structural units.
[0052] The obtained fluorine-containing polymer powder was added into a twin-screw extruder, the temperature of the screw heating section was set to 200°C, 210°C and 220°C respectively, and the rods were prepared by heating and extruding through a circular die. The rods were passed into a plastic crusher and crushed into pellets.
[0053] Fluorine-containing polymer pellets were added to the twin-screw extruder, and the temperatures of the screw heating section were set to 200°C, 210°C and 220°C, respectively. The fluorine-containing polymer pellets were extruded through a flat die in a molten state to obtain a 150 μm sheet. The extruded polymer sheet was pulled and uniaxially stretched in the stretching section with a stretching ratio of 6 to obtain a 30 μm polarization film.
[0054] The film was spread flat on the negative electrode plate with a distance of 5 mm from the discharge needle. The frequency was 1 Hz and the electric field strength amplitude was gradually increased from 0 to 400 MV / m of alternating current and maintained for 80 seconds. The electric field was then removed to obtain a prepolarized polymer film. The piezoelectric strain constant was tested to be 28.3 pm / V.
[0055] The film was placed in an ice water bath and fixed to the bottom of the container with double-sided tape. The ultrasonic probe was inserted 2 mm above the film. The output power of the probe was set to 300 W, and the working mode was set to work for 5 s every 6 s for 20 min. After ultrasonic polarization, the film was taken out and dried. The piezoelectric strain constant was tested to be 34.4 pm / V.
[0056] Example 3: P(VDF-VCZ)-98 / 2
[0057] 3000mL of deionized water, 1g of hydroxypropyl methylcellulose as a dispersant, 3g of ethyl acetate as a polymerization agent and 80g of N-vinyl carbazole were added to the reactor, the reactor was closed and replaced with nitrogen three times. 1200g of vinylidene fluoride was added to the reactor respectively, and then the temperature was raised. When the temperature rose to 40°C, 5g of diisopropyl peroxydicarbonate was added to the reactor as an initiator to initiate the polymerization reaction. The initial reaction pressure was 6.8MPa, and the reaction temperature was maintained at 40°C. The reaction was terminated when the pressure dropped to 2.5MPa. After the polymerization was completed, fluorine-containing polymer powder was obtained by washing, dehydration and drying. The fluorine-containing polymer obtained by nuclear magnetic resonance characterization contains 2mol% N-vinyl carbazole copolymer structural units.
[0058] The obtained fluorine-containing polymer powder was added into a twin-screw extruder, the temperature of the screw heating section was set to 200°C, 210°C and 220°C respectively, and the rods were prepared by extrusion through a circular die. The rods were passed into a plastic crusher and crushed into pellets.
[0059] Fluorine-containing polymer pellets were added to the twin-screw extruder, and the temperatures of the screw heating section were set to 200°C, 210°C and 220°C, respectively. The fluorine-containing polymer pellets were extruded through a flat die in a molten state to obtain a 150 μm sheet. The extruded polymer sheet was pulled and uniaxially stretched in the stretching section with a stretching ratio of 6 to obtain a 30 μm polarization film.
[0060] The film was spread flat on the negative electrode plate with a distance of 5 mm from the discharge needle. The frequency was 1 Hz and the amplitude of the electric field strength gradually increased from 0 to 400 MV / m of alternating current and maintained for 80 seconds. The electric field was then removed to obtain a prepolarized polymer film. The piezoelectric strain constant was tested to be 33.0 pm / V.
[0061] The film was placed in an ice water bath and fixed to the bottom of the container with double-sided tape. The ultrasonic probe was inserted 2 mm above the film. The output power of the probe was set to 300 W. The working mode was 5 s every 6 s for 20 min. After ultrasonic polarization, the film was taken out and dried. The piezoelectric strain constant was tested to be 48.7 pm / V.
[0062] Example 4: P(VDF-VCZ)-95 / 5
[0063] 3000mL of deionized water, 1g of hydroxypropyl methylcellulose as a dispersant, 3g of ethyl acetate as a telogen and 200g of N-vinyl carbazole were added to the reactor, the reactor was closed and replaced with nitrogen three times. 1200g of vinylidene fluoride was added to the reactor respectively, and then the temperature was raised. When the temperature rose to 40°C, 5g of diisopropyl peroxydicarbonate was added to the reactor as an initiator to initiate the polymerization reaction. The initial reaction pressure was 6.8MPa. The reaction temperature was maintained at 40°C, and the reaction was terminated when the pressure dropped to 2.5MPa. After the polymerization was completed, the fluorinated polymer powder was obtained by washing, dehydration and drying. The fluorinated polymer obtained by nuclear magnetic resonance characterization contained 5mol% N-vinyl carbazole copolymer structural units.
[0064] Fluorine-containing polymer powder was added into a twin-screw extruder, the temperature of the screw heating section was set to 200°C, 210°C and 220°C respectively, and the powder was extruded through a circular die to prepare rods. The rods were passed into a plastic crusher and crushed to prepare pellets.
[0065] Fluorine-containing polymer pellets were added to the twin-screw extruder, and the temperatures of the screw heating section were set to 200°C, 210°C and 220°C, respectively. The fluorine-containing polymer pellets were extruded through a flat die in a molten state to obtain a 150 μm sheet. The extruded polymer sheet was pulled and uniaxially stretched in the stretching section with a stretching ratio of 6 to obtain a 30 μm polarization film.
[0066] The film was spread flat on the negative electrode plate with a distance of 5 mm from the discharge needle. The frequency was 1 Hz and the electric field strength amplitude was gradually increased from 0 to 400 MV / m of alternating current and maintained for 80 seconds. The electric field was then removed to obtain a prepolarized polymer film. The tested piezoelectric strain constant was 38.5 pm / V.
[0067] The film was placed in an ice water bath and fixed to the bottom of the container with double-sided tape. The ultrasonic probe was inserted 2 mm above the film. The output power of the probe was set to 300 W. The working mode was 5 s every 6 s for 20 min. After ultrasonic polarization, the film was taken out and dried. The piezoelectric strain constant was tested to be 60.2 pm / V.
[0068] Example 5: P(VDF-2-vinylnaphthalene)-95 / 5
[0069] 3000mL of deionized water, 1g of hydroxypropyl methylcellulose as a dispersant, 3g of ethyl acetate as a telogen and 152g of 2-vinylnaphthalene were added to the reactor, the reactor was closed and replaced with nitrogen three times. 1200g of vinylidene fluoride was added to the reactor respectively, and then the temperature was raised. When the temperature rose to 40°C, 5g of diisopropyl peroxydicarbonate was added to the reactor as an initiator to initiate the polymerization reaction. The initial reaction pressure was 6.8MPa, and the reaction temperature was maintained at 40°C. The reaction was terminated when the pressure dropped to 2.5MPa. After the polymerization was completed, fluorine-containing polymer powder was obtained by washing, dehydration and drying. The polymer obtained by nuclear magnetic characterization contained 5mol% 2-vinylnaphthalene copolymerization structural units.
[0070] Fluorine-containing polymer powder was added into a twin-screw extruder, the temperature of the screw heating section was set to 200°C, 210°C and 220°C respectively, and the powder was extruded through a circular die to prepare rods. The rods were passed into a plastic crusher and crushed to prepare pellets.
[0071] Fluorine-containing polymer pellets were added to the twin-screw extruder, and the temperatures of the screw heating section were set to 200°C, 210°C and 220°C, respectively. The fluorine-containing polymer pellets were extruded through a flat die in a molten state to obtain a 150 μm sheet. The extruded polymer sheet was pulled and uniaxially stretched in the stretching section with a stretching ratio of 6 to obtain a 30 μm polarization film.
[0072] The film was spread flat on the negative electrode plate with a distance of 5 mm from the discharge needle. The frequency was 1 Hz and the amplitude of the electric field strength was gradually increased from 0 to 400 MV / m of alternating current and maintained for 80 seconds. The electric field was then removed to obtain a prepolarized fluoropolymer film. The piezoelectric strain constant was tested to be 36.8 pm / V.
[0073] The film was placed in an ice water bath and fixed to the bottom of the container with double-sided tape. The ultrasonic probe was inserted 2 mm above the film. The output power of the probe was set to 300 W, and the working mode was set to work for 5 s every 6 s for 20 min. After ultrasonic polarization, the film was taken out and dried. The piezoelectric strain constant was tested to be 56.9 pm / V.
[0074] Example 6: P(VDF-3-vinylthiophene)-95 / 5
[0075] 3000mL of deionized water, 1g of hydroxypropyl methylcellulose as a dispersant, 3g of ethyl acetate as a telogen and 109g of 3-vinylthiophene were added to the reactor, the reactor was closed and replaced with nitrogen three times. 1200g of vinylidene fluoride was added to the reactor respectively, and then the temperature was raised. When the temperature rose to 40°C, 5g of diisopropyl peroxydicarbonate was added to the reactor as an initiator to initiate the polymerization reaction. The initial reaction pressure was 6.8MPa, and the reaction temperature was maintained at 40°C. The reaction was terminated when the pressure dropped to 2.5MPa. After the polymerization was completed, fluorine-containing polymer powder was obtained by washing, dehydration and drying. The fluorine-containing polymer obtained by nuclear magnetic resonance characterization contains 5mol% 3-vinylthiophene copolymer structural units.
[0076] Fluorine-containing polymer powder was added into a twin-screw extruder, the temperature of the screw heating section was set to 200°C, 210°C and 220°C respectively, and the powder was extruded through a circular die to prepare rods. The rods were passed into a plastic crusher and crushed to prepare pellets.
[0077] Fluorine-containing polymer pellets were added to the twin-screw extruder, and the temperatures of the screw heating section were set to 200°C, 210°C and 220°C, respectively. The fluorine-containing polymer pellets were extruded through a flat die in a molten state to obtain a 150 μm sheet. The extruded polymer sheet was pulled and uniaxially stretched in the stretching section with a stretching ratio of 6 to obtain a 30 μm polarization film.
[0078] The film was spread flat on the negative electrode plate with a distance of 5 mm from the discharge needle. The frequency was 1 Hz and the electric field strength amplitude was gradually increased from 0 to 400 MV / m of alternating current and maintained for 80 seconds. The electric field was then removed to obtain a prepolarized fluoropolymer film. The piezoelectric strain constant was tested to be 31.9 pm / V.
[0079] The film was placed in an ice water bath and fixed to the bottom of the container with double-sided tape. The ultrasonic probe was inserted 2 mm above the film. The output power of the probe was set to 300 W. The working mode was 5 s every 6 s for 20 min. After ultrasonic polarization, the film was taken out and dried. The piezoelectric strain constant was tested to be 42.6 pm / V.
[0080] Example 7: P(VDF-2-vinylanthracene)-95 / 5
[0081] 3000mL of deionized water, 1g of hydroxypropyl methylcellulose as a dispersant, 3g of ethyl acetate as a telogen and 203g of 2-vinyl anthracene were added to the reactor, the reactor was closed and replaced with nitrogen three times. 1200g of vinylidene fluoride was added to the reactor respectively, and then the temperature was raised. When the temperature rose to 40°C, 5g of diisopropyl peroxydicarbonate was added to the reactor as an initiator to initiate the polymerization reaction. The initial reaction pressure was 6.8MPa, and the reaction temperature was maintained at 40°C. The reaction was terminated when the pressure dropped to 2.5MPa. After the polymerization was completed, fluorine-containing polymer powder was obtained by washing, dehydration and drying. The fluorine-containing polymer obtained by nuclear magnetic characterization contains 5mol% 2-vinyl anthracene copolymer structural units.
[0082] Fluorine-containing polymer powder was added into a twin-screw extruder, the temperature of the screw heating section was set to 200°C, 210°C and 220°C respectively, and the powder was extruded through a circular die to prepare rods. The rods were passed into a plastic crusher and crushed to prepare pellets.
[0083] Fluorine-containing polymer pellets were added to the twin-screw extruder, and the temperatures of the screw heating section were set to 200°C, 210°C and 220°C, respectively. The fluorine-containing polymer pellets were extruded through a flat die in a molten state to obtain a 150 μm sheet. The extruded polymer sheet was pulled and uniaxially stretched in the stretching section with a stretching ratio of 6 to obtain a 30 μm polarization film.
[0084] The film was spread flat on the negative electrode plate with a distance of 5mm between it and the discharge needle. The frequency was 1Hz and the amplitude of the electric field strength gradually increased from 0 to 400MV / m of alternating current and maintained for 80s. The electric field was then removed to obtain a polarization film. The piezoelectric strain constant was tested to be 34.0pm / V.
[0085] The film was placed in an ice water bath and fixed to the bottom of the container with double-sided tape. The ultrasonic probe was inserted 2 mm above the film. The output power of the probe was set to 300 W. The working mode was 5 s every 6 s for 20 min. After ultrasonic polarization, the film was taken out and dried. The piezoelectric strain constant was tested to be 49.1 pm / V.
[0086] Comparative Example 1: PVDF piezoelectric film
[0087] PVDF pellets were added to the twin-screw extruder, and the temperatures of the screw heating section were set to 200°C, 210°C and 220°C, respectively. The polymer resin was extruded through a flat die in a molten state to obtain a 150 μm sheet. The extruded PVDF sheet was pulled and uniaxially stretched in the stretching section with a stretching ratio of 6 to obtain a 30 μm polarization film.
[0088] The film was spread flat on the negative electrode plate with a distance of 5 mm from the discharge needle. The frequency was 1 Hz and the electric field strength amplitude was gradually increased from 0 to 400 MV / m of alternating current and maintained for 80 seconds. The electric field was then removed to obtain a prepolarized PVDF film. The tested piezoelectric strain constant was 22.0 pm / V.
[0089] The film was placed in an ice water bath and fixed to the bottom of the container with double-sided tape. The ultrasonic probe was inserted 2 mm above the film. The output power of the probe was set to 300 W. The working mode was 5 s every 6 s for 20 min. After ultrasonic polarization, the film was taken out and dried. The piezoelectric strain constant was tested to be 22.0 pm / V.
[0090] Comparative Example 2: P(VDF-TrFE)-Optimal Ratio
[0091] FC50 P (VDF-TrFE) polymer pellets produced by Arkema were added to the twin-screw extruder, the temperatures of the screw heating section were set to 170°C, 180°C and 190°C respectively, and the polymer resin was extruded in a molten state through a flat die to obtain a 30 μm polarization film.
[0092] The film was spread flat on the negative electrode plate with a distance of 5mm between it and the discharge needle. The frequency was 1Hz and the amplitude of the electric field strength gradually increased from 0 to 400MV / m of alternating current and maintained for 80s. The electric field was then removed to obtain a polarization film. The piezoelectric strain constant was tested to be 63.5pm / V.
[0093] The film was placed in an ice water bath and fixed to the bottom of the container with double-sided tape. The ultrasonic probe was inserted 2 mm above the film. The output power of the probe was set to 300 W. The working mode was 5 s every 6 s for 20 min. After ultrasonic polarization, the film was taken out and dried. The piezoelectric strain constant was tested to be 63.5 pm / V.
[0094] The performance data of the fluorine-containing polymers and films prepared in the examples and comparative examples are shown in Table 1.
[0095] Table 1 Performance data of fluorinated polymers and piezoelectric films prepared in Examples and Comparative Examples
[0096]
[0097]
[0098] Example 8
[0099] Same as Example 4, except that: after obtaining the prepolarized polymer film, ultrasonic polarization is performed at different ultrasonic powers of 0 to 400 W. The piezoelectric strain constants of the piezoelectric films obtained by ultrasonic polarization at different ultrasonic powers are shown in Figure 1 .from Figure 1 It can be seen that under the ultrasonic power of 0-100W, the piezoelectric strain constant is almost unchanged; under the ultrasonic power of 100-300W, the piezoelectric strain constant increases with the increase of ultrasonic power; when the ultrasonic power exceeds 300W, the piezoelectric strain constant decreases instead. This is because excessive ultrasonic power causes irreversible physical damage to the film.
[0100] Example 9
[0101] Same as Example 4, except that: after the pre-polarized polymer film is obtained, the ultrasonic time is from 0 to 40 min at 300 W ultrasonic power. The piezoelectric strain constant of the piezoelectric film obtained by ultrasonic polarization at different ultrasonic times is shown in Figure 2 .from Figure 2 It can be seen that from 0 to 20 minutes, the piezoelectric strain constant increases with the increase of ultrasonic time, but decreases with the increase of ultrasonic time after 20 minutes. This is because the long-term ultrasonic field action causes too many permanent structural defects to form inside the polymer, which seriously destroys the formation of ferroelectric domains inside the material.
Claims
1. A fluorine-containing polymer, characterized in that: The fluorine-containing polymer comprises a vinylidene fluoride structural unit and a photoelectric conjugated compound structural unit, and the photoelectric conjugated compound is selected from at least one of N-vinyl carbazole, vinyl naphthalene, vinyl thiophene or vinyl anthracene.
2. The fluorinated polymer according to claim 1, characterized in that: The content of the photoelectric conjugated compound structural unit is 0.5-10 mol%.
3. The fluorinated polymer according to claim 2, characterized in that: The content of the photoelectric conjugated compound structural unit is 1 to 5 mol%.
4. The fluorinated polymer according to claim 1, characterized in that: The vinylnaphthalene is selected from at least one of 1-vinylnaphthalene and 2-vinylnaphthalene; the vinylthiophene is selected from at least one of 2-vinylthiophene and 3-vinylthiophene; the vinylanthracene is selected from at least one of 1-vinylanthracene, 2-vinylanthracene or 9-vinylanthracene.
5. A method for preparing a fluorine-containing polymer according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) adding deionized water, a dispersant, a telogen, and a photoelectric conjugated compound accounting for 1.64 to 14.29 wt % of the total amount of the photoelectric conjugated compound and vinylidene fluoride into a reaction kettle, and replacing the reaction kettle with nitrogen; (2) adding 98.36 to 85.71 wt % of the total amount of the photoelectric conjugated compound and the vinylidene fluoride into the reaction kettle, and then starting to raise the temperature to 35 to 50° C.; (3) Adding an initiator to the reactor, maintaining the polymerization reaction temperature at 35-50° C. and the initial pressure at 5.8-7.0 MPa, and when the pressure drops to 2.5 MPa, ending the polymerization reaction, washing, dehydrating, and drying to obtain a fluorine-containing polymer.
6. A piezoelectric film, characterized in that: The piezoelectric film comprises the fluorine-containing polymer according to any one of claims 1-4.
7. A method for preparing a piezoelectric film containing a fluorine-containing polymer according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1: The fluorinated polymer is extruded in a molten state to obtain a fluorinated polymer sheet, which is then stretched to obtain a fluorinated polymer film; S2: After the fluorine-containing polymer film is polarized in an alternating electric field, it is polarized for a second time under ultrasonic conditions with a power of 250 to 350 W for 18 to 30 minutes to obtain a fluorine-containing polymer piezoelectric film.
8. The method for preparing a piezoelectric film of a fluorine-containing polymer according to claim 7, characterized in that: In S1, the thickness of the fluorine-containing polymer sheet is 100-200 μm, the stretching ratio of the fluorine-containing polymer sheet is 3-6 times, and the thickness of the fluorine-containing polymer film is 20-70 μm.
9. The method for preparing a piezoelectric film of a fluorine-containing polymer according to claim 7, characterized in that: In S2, the frequency of the AC electric field is 0.5-5 Hz, and the intensity of the AC electric field is ≥400 MV / m.
10. The method for preparing a piezoelectric film of a fluorine-containing polymer according to claim 7, characterized in that: In S2, the polarization period of the fluorine-containing polymer film under an alternating electric field is ≥40.
Citation Information
Patent Citations
Piezoelectric film and method for producing same
CN110462859A